Neurological Effect of Lead Exposure in Children (Medicine Today, 2013)
Lead poisoning is one of the burning issues in Bangladesh. This study assessed the relation of blood lead level with IQ and peripheral nerve function in environmental lead exposed primary school children in Dhaka.Blood lead level (BLL) was measured in 84 primary school children in an urban industrial area of Dhaka. IQ was measured with Wechsler Intelligence Scales- Revised for children. Electrophysiological evaluation was done in 31 children.Verbal, Performance and Full scale IQ had a negative correlation with blood lead level (p